Changes in corneal higher-order aberrations following PreserFlo MicroShunt implantation - Taro Baba; Kazuyuki Hirooka; Naoki Okada; Hiromitsu Onoe; Kana Tokumo; Hideaki Okumichi; Yoshiaki Kiuchi; Hirokazu Sakaguchi (Scientific Reports)
Abstract In this retrospective study, we evaluated changes in corneal higher-order aberrations (HOAs) after PreserFlo MicroShunt (PFM) implantation and examined factors associated with the outcomes. We included 101 PFM implantations performed between February 2023 and June 2024. Visual acuity, intraocular pressure, corneal HOAs, and coma-like and spherical aberrations were analyzed preoperatively, at 1 week, and at 1, 2, and 3 months postoperatively. Generalized linear mixed models were used to analyze factors that might affect HOAs and other aberrations. Preoperatively, HOAs, coma-like aberrations, and spherical-like aberrations were 0.249 ± 0.192, 0.216 ± 0.180, and 0.109 ± 0.093 μm, respectively. Aberrations showed a significant increase up to 1 month postoperatively, peaking at 1 week, with values of 0.396 ± 0.210 μm, 0.346 ± 0.204 μm, and 0.173 ± 0.105 μm, respectively (all P < 0.001). The aberrations were no longer significantly greater than baseline at 2 and 3 months postoperatively. Analysis of risk factors suggested that post-implantation hypotony (≤ 5 mmHg) could influence corneal HOAs and coma-like aberrations. PFM implantation temporarily increased corneal HOAs, coma-like aberrations, and spherical aberrations, but these levels stabilized and had returned to preoperative levels by 2 months postoperatively. Postoperative hypotony was associated with increased corneal HOAs and coma-like aberrations.